Is depression a concern among medical students: a cross sectional study in different academic years of a private medical college in Bangladesh - Hamid, Farzana; Moosa, Syed Ahmad; Quaium, Syed Moosa M.A.; Haque, A. K. Fazlul (International Journal of Research in Medical Sciences, 2020)
Background: Depression is not uncommon among medical students all over the world. Few studies have been conducted so far in Bangladesh to depict its actual prevalence and severity. So, the aim of this study was to assess the severity of depression and the level of difficulty faced by medical students in different academic years. Methods: This cross-sectional study was conducted in North East medical college of Bangladesh from January 2018 to June 2018 involving 443 students from 1st year to 5th year. Students were instructed to fill up the patient health questionnaire (PHQ-9) which incorporates diagnostic and statistical manual of mental disorders (DSM-IV) depression diagnostic criteria categorized as no, mild, moderate, moderately severe, and severe depression and also evaluates their level of function. Results: The prevalence of depression was quite high (79.68%). 196 (44.24%) and 157 (35.44%) students had mild and major depression respectively, while 90 (20.32%) showed no depression. Students with major depression were scored as moderate depression 24.38%, moderately severe depression 8.35%, and severe depression 2.71%. Moderate depression was significantly higher in year 1 and year 2 students in comparison to year 3, 4 and 5. Students from year 1 to year 5 with mild, moderate, moderately severe and severe depression experienced varying degree of difficulty in their daily activities. Almost all the students in all years with severe depression found themselves very difficult or extremely difficult to cope. Conclusions: High prevalence of depression among medical students is really alarming and underlying factors need to be addressed.